Effective Rust 35 specific ways to improve your Rust code - Drysdale, David (O'Reilly Media, Inc., 2024)
Rust's popularity is growing, due in part to features like memory safety, type safety, and thread safety. But these same elements can also make learning Rust a challenge, even for experienced programmers. This practical guide helps you make the transition to writing idiomatic Rust-while also making full use of Rust's type system, safety guarantees, and burgeoning ecosystem. If you're a software engineer who has experience with an existing compiled language, or if you've struggled to convert a basic understanding of Rust syntax into working programs, this book is for you. By focusing on the conceptual differences between Rust and other compiled languages, and by providing specific recommendations that programmers can easily follow, Effective Rust will soon have you writing fluent Rust, not just badly translated C++.
Includes bibliographical references and index
Keywords: Rust (Computer program language); Rust (Langage de programmation)